Livestock innovations for greater economic good - International Livestock Research Institute (International Livestock Research Institute, 2019)
This film describes how every one of the world's many livestock systems is being transformed by innovations in livestock development: research innovations, technological innovations, policy innovations and political will to drive economic development.